1996
DOI: 10.1095/biolreprod55.5.1147
|View full text |Cite
|
Sign up to set email alerts
|

Nonluteal Estrous Cycles of 3-Week Duration are Initiated by Anovulatory Luteinizing Hormone Peaks in African Elephants

Abstract: Previous attempts to characterize the estrous cycle of elephants have yielded conflicting estimates of cycle length and LH profiles. In order to establish artificial breeding programs in this species, resolution of these issues is needed. Therefore, four female African elephants housed at the Indianapolis Zoo were studied for approximately 6 mo beginning in December 1994. Blood was collected weekly, and the serum was immediately analyzed for progesterone (P4). Whenever the weekly concentration of P4 was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 8 publications
7
49
0
2
Order By: Relevance
“…FSH may well serve that purpose in elephants; however, the unusually protracted profile along with the long follicular phase of the elephant (up to 6 weeks) makes species comparisons difficult. The finding of two LH surges, the first anovulatory and the second ovulatory, occurring 3 weeks apart during the follicular phase of the cycle also was similar to earlier reports for both species (Brown et al, 1999b;Kapustin et al, 1996). The ability to conduct a direct species comparison for LH in this study revealed that while baseline concentrations did not differ, LH surges were of greater magnitude on average in Asian elephants.…”
Section: Discussionsupporting
confidence: 90%
“…FSH may well serve that purpose in elephants; however, the unusually protracted profile along with the long follicular phase of the elephant (up to 6 weeks) makes species comparisons difficult. The finding of two LH surges, the first anovulatory and the second ovulatory, occurring 3 weeks apart during the follicular phase of the cycle also was similar to earlier reports for both species (Brown et al, 1999b;Kapustin et al, 1996). The ability to conduct a direct species comparison for LH in this study revealed that while baseline concentrations did not differ, LH surges were of greater magnitude on average in Asian elephants.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, a slight, transient rise in urinary PdG concentrations occurred the day following that oestrus and may be useful in predicting ovulation. Even though Kasman et al (1986) were unable to verify ovulation through the methods used in their study, they reported a similar rise in urinary PdG concentrations up to 5 days prior to the decline in urinary E 1 C. Progesterone has been implicated to play a role in ovulation in many other mammalian species (Kapustin et al 1996, Zalanyi 2001, Cassar et al 2002, Jo et al 2002, Stouffer 2002.…”
Section: Discussionmentioning
confidence: 89%
“…6,25 Elephants are unique in having the longest documented mammalian estrous cycle, of 13-17 wk, and exhibiting two successive waves of follicular development that culminate in two distinct LH surges, with only the second inducing ovulation. 8,9,35 One documented problem of older female elephants and other long-lived species in captivity is termed asymmetric reproductive aging. 24,28 In the wild, most adult female elephants are either pregnant or lactating; they experience comparatively few reproductive cycles in their lifetime.…”
Section: Introductionmentioning
confidence: 99%